How Does the Impact of an HIV/AIDS Information Campaign Vary with Educational Attainment? Evidence from Rural Uganda - De Walque, Damien (World Bank, Washington, D.C., 2013)
The responsiveness to information is thought to be one channel through which education affects health outcomes. The author tests this hypothesis by examining the effectiveness of an information campaign that aims at preventing the HIV/AIDS epidemic in Uganda. Previous studies in the epidemiological literature have generally concluded that, in Africa, there was either a positive association or no association between HIV infection and schooling levels. Using individual level data from a cohort study following the general population of a cluster of villages in rural Uganda over 12 years, the author shows that, after more than a decade of prevention campaigns about the dangers of the epidemic, there has been a substantial evolution in the HIV/education gradient. Early in the epidemic, in 1990, there was no robust relation between HIV/AIDS and education. In 2000, among young individuals, in particular among females, education lowers the risk of being HIV positive. Results on HIV incidence in a duration framework confirm that finding by establishing that, for young individuals, education reduces the probability of seroconversion. These findings reveal that educated individuals have been more responsive to the HIV/AIDS information campaigns. The analysis of sexual behavior reinforces that conclusion: condom use is associated positively with schooling levels.